2008
DOI: 10.1002/asi.20956
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of service quality and continuance intention of online services: The case of eTax

Abstract: This article examines the determinants of service quality and continuance intention of online services. We proposed and empirically tested a model with both service and technology characteristics as the main drivers of service quality and subsequent continuance intention of eTax, an electronic government (eGovernment) service that enables citizens to file their taxes online. Our data were collected via a two-stage longitudinal online survey of 518 participants before and after they made use of the eTax service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
75
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 132 publications
6
75
1
5
Order By: Relevance
“…Hu et al (2009) state that e-service quality is jointly determined by service characteristics and technology characteristics. They, in identifying the dimensions of service quality of online tax services in Hong Kong, adapted SERVQUAL for the service characteristics.…”
Section: Previous Research On Service Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Hu et al (2009) state that e-service quality is jointly determined by service characteristics and technology characteristics. They, in identifying the dimensions of service quality of online tax services in Hong Kong, adapted SERVQUAL for the service characteristics.…”
Section: Previous Research On Service Qualitymentioning
confidence: 99%
“…One of the major factors which influence a person"s decision to adopt e-services is the quality of that service (Rotchanakitumnuai, 2008). Asubonteng and McClearly (1996), Hu, Brown, Thong, Chan, and Tam (2009) and Pinho, De Lurdis Martins and Macedo (2011) found that increased service quality also increases the intention to reuse the specific service.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies [20,24,29,52,58] used TAM and TPB together, four of them [6,24,48,77] used even three theories or models, whereas three [32,68,74] Survey: [6], [8], [9], [12], [16], [20], [24], [29], [32], [48], [49], [52], [58], [63], [67], [68], [74], [77], [76], [79], [86]; Interview: [84], [86], [89]; Secondary Data Analysis: [31]; Case Study: [69] Information System Success Model (DeLone and McLean, 1992McLean, , 2003 Survey: [19], [22], [30], [32], [55], [59], [65], [68], [74], …”
Section: Resultsmentioning
confidence: 99%
“…However, despite a lot of interest being drawn into eGovernment, the field is criticized for not having a common definition of e-Government (Hu et al 2009) and also generally lacking clarity and rigor about the factors contributing to its implementation alongside poor treatment of generalization (Heeks and Bailur, 2007). Furthermore, recently, researchers and other stakeholders affected by the eGovernment innovation's impacts have started raising concerns on its high reported failure rates (Heeks and Bailur, 2007).…”
Section: Introduction 11 Background Of the Studymentioning
confidence: 99%